The de facto routes as a cause of illegality of the actions of the Public Administration in Chile. Recognition, fundamentals and consequences (Justicia &Derecho, 2025)
The de facto means constitute actions of the State Administration that do not find support in the principle of legality, which only have implicit recognition in the Chilean legal system. Despite the importance of this institution for the control of the material activity of the Administration bodies and the serious consequences that it entails, its application in national environment is scarce. Thus, this article proposes a brief review of its recognition, its normative foundations, as well as its consequences in order to promote its practical operation.
Keywords: ways of fact; administrative action; administrative act; Public Administration; principle of legality